DAMPAK EMPLOYEE BRANDING PADA EFEKTIVITAS REKRUTMEN (Case Study: Generasi Z Indonesia) - Stefanus Rumangkit; Muhammad Dwiyan (Jurnal Bisnis Darmajaya, 2019)
This study aims to examine the effect of employee branding on job seekers' interest in participating in the recruitment process. This is based on the shift of the Indonesian workforce from generation Y to generation X. Respondents in the study amounted to 300 respondents. The sampling technique uses purposive sampling. Testing instruments using validity and reliability tests. Tests of data analysis using multiple regression analysis with hypothesis testing using Test T. The results of this study, namely: 1) Interest value affects the interest of job seekers to follow the recruitment process, 2) Social value affects the interest of job seekers to follow the recruitment process, 3) social value influences the interest of job seekers to participate in the recruitment process, 4) development value influences the interest of job seekers to participate in the recruitment process, 5) applicant value influences the interest of job seekers to participate in the recruitment process. Keywords — Employee Branding, Rekrutment, Selection, Job Seeker